Selawatan Sebagai Seni Pertunjukan Musikal - Andre Indrawan (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2010)
The Selawatan as Musical Performance. The selawatan, an Indonesian Islamic performing arts genre, has beenlooked at from different study perspectives. Although mostly understood as a group type of folk dances as well astheatres, this study has found that the selawatan in the DIY is closely related to an Islamic musical genre which wasbased on vocal art. The most important characteristic that relates amongst any types of selawatan is its repertoirematerials which is centered to a classical Arabic text known as mawlid, especially the one that was written by Al-Barzanji.